2010
DOI: 10.1002/eji.200939613
|View full text |Cite
|
Sign up to set email alerts
|

In vivo depletion of CD4+FOXP3+ Treg cells by the PC61 anti‐CD25 monoclonal antibody is mediated by FcγRIII+ phagocytes

Abstract: Depletion of CD4 1 CD25 1 FoxP3 1 Treg using PC61 mAb (anti-murine CD25 rat IgG1) is widely used to characterize Treg function in vivo. However, the mechanism of Treg depletion remains largely unknown. Herein, we report the PC61 mAb's mechanism of action. In peripheral blood, a single injection of PC61 mAb eliminated $70% of CD4 1 FoxP3 1 cells with the remaining Treg expressing low or no CD25. Functional blockade of Fcc receptors with 2.4G2 mAb significantly inhibited PC61 mAb activity. Furthermore, Fcc recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
180
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(200 citation statements)
references
References 36 publications
18
180
0
Order By: Relevance
“…The difference in the absolute numbers of Tregs between TRAIL 2/2 mice and WT mice was significant on day 7 for the spleen (Table III We first analyzed the degree of reduction in Foxp3 + Tregs after injection of anti-CD25 mAb. Consistent with previous reports (27), the injection of anti-CD25 mAb reduced Foxp3 + Tregs in the spleen to less than half of the control levels in both types of mice (Fig. 4A, 4B).…”
Section: Increased Numbers Of Ifn-g-producing Cd4supporting
confidence: 92%
“…The difference in the absolute numbers of Tregs between TRAIL 2/2 mice and WT mice was significant on day 7 for the spleen (Table III We first analyzed the degree of reduction in Foxp3 + Tregs after injection of anti-CD25 mAb. Consistent with previous reports (27), the injection of anti-CD25 mAb reduced Foxp3 + Tregs in the spleen to less than half of the control levels in both types of mice (Fig. 4A, 4B).…”
Section: Increased Numbers Of Ifn-g-producing Cd4supporting
confidence: 92%
“…To further test this hypothesis, we used neutralizing antibodies against CD25 or Ly6G to deplete Tregs or G-MDSCs, respectively, in mice bearing 4T1 tumors (23)(24)(25). We found that anti-Ly6G, when used in combination with anti-PD-1/anti-CTLA-4 antibodies, was as effective as the epigenetic modulators (Fig.…”
Section: Significancementioning
confidence: 98%
“…As an alternative approach to examining the actions of Tregs, we tested previously published Treg depletion strategies (anti-CD25, anti-FR4) (47,48). However, when these treatments were initiated prior to the second challenge in the dual-challenge CS model used in this study, they were ineffective in selective Treg depletion (data not shown).…”
Section: Reduction Of Treg Adhesion Via Icam-1 Inhibition Is Associatmentioning
confidence: 99%